2013
DOI: 10.5115/acb.2013.46.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of elastic fibers in the head and neck: a histological study using late-stage human fetuses

Abstract: There is little or no information about the distribution of elastic fibers in the human fetal head. We examined this issue in 15 late-stage fetuses (crown-rump length, 220-320 mm) using aldehyde-fuchsin and elastica-Masson staining, and we used the arterial wall elastic laminae and external ear cartilages as positive staining controls. The posterior pharyngeal wall, as well as the ligaments connecting the laryngeal cartilages, contained abundant elastic fibers. In contrast with the sphenomandibular ligament an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The computer analysis may not able to discriminate the differences between sinusoidal and arterial endothelium. EM staining enabled us to identify unpaired arteries by detecting smooth muscle and elastic fibers . Furthermore, we identified sinusoid‐like microvessels in approximately 15% of all cases in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The computer analysis may not able to discriminate the differences between sinusoidal and arterial endothelium. EM staining enabled us to identify unpaired arteries by detecting smooth muscle and elastic fibers . Furthermore, we identified sinusoid‐like microvessels in approximately 15% of all cases in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The number of elastic fibers was found to be larger in the peritoneum than in the adjacent fascial structures [ 11 , 12 ]. Because of the pleural and/or peritoneal remnants in the mesoesophagus, the esophageal hiatus seems to carry elastic fibers at the 10th week [ 13 ], much earlier than other tissues [ 14 ]. Surgeons have been interested in the morphology of the phrenoesophageal membrane (=the phrenicoesophageal ligament), a dome-like membrane surrounding the lower thoracic esophagus just above the esophageal hiatus (e.g., St Peter et al [ 15 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using elastica-Masson staining (a variation of Masson-Goldner staining), we examined whether or not the fetal pleura contains elastic fibers. According to Kinoshita et al [ 8 ], who demonstrated initial appearance of elastic fibers in the fetal head and neck, we expected to find elastic fibers in the lung after gestational week 20. Consequently, the aim of this study was to describe the fetal pulmonary pleura in relation to the lung surface morphology.…”
Section: Introductionmentioning
confidence: 96%